Reality Group Counseling to Increase Students' Learning Responsibility: Effective or Not? - Nova Setyawan; Abi F. Prabawa (Indonesian Journal of Guidance and Counseling: Theory and Application, 2024)
The low level of learning responsibility that occurs in students needs to be given immediate service intervention. This research aims to test the effectiveness of reality group counseling service intervention to increase students' learning responsibility. The method used is a pre-experiment group pretest-post-test design. Data collection used a learning responsibility scale adapted from Aisyah, et al. (2014) and the elaboration of Deni & Ismaniar (2022). 41 items passed the validity and reliability tests and were divided into two types, A and B, each consisting of 26 items. All items had a validity value >0.3 and a reliability value of 0.93. The participants of this study were 11 students. The participants of this study were 11 students. The sampling technique in this research uses a purposive sampling technique. Hypothesis testing in this research uses paired samples t-test. Based on the results of hypothesis testing, p =,013 (p < 0.05) was obtained, meaning that reality group counseling services are effective for increasing students' learning responsibilities. The limitations of this study are the limited number of participants so that in generalizing the results of the study, caution needed, and the inclusion of Islamic-based elements in reality group counseling has the potential to limit the generalization of the results of this study in all religions. Future researchers are advised to use a larger population, including students with diverse religious backgrounds, and explore reality group counseling without Islamic elements to determine its impact on the learning responsibility of students from various religious backgrounds. Rendahnya tingkat tanggung jawab belajar yang terjadi pada siswa perlu untuk segera diberikan intervensi layanan. Riset ini bertujuan untuk menguji efektivitas intervensi layanan konseling kelompok realita untuk meningkatkan tanggung jawab belajar siswa. Metode yang digunakan yaitu pre-eksperimen one group pretest-post test design. Pengumpulan data menggunakan skala tanggung jawab belajar yang diadaptasi dari Aisyah, dkk. (2014) dan elaborasi Deni & Ismaniar (2022). Terdapat 41 item lulus uji validitas dan reliabilitas dan dibagi menjadi dua jenis, A dan B, masing-masing terdiri dari 26 item. Semua item memiliki nilai validitas > 0,3 dan nilai reliabilitas 0,93. Partisipan dari penelitian ini adalah 11 siswa. Partisipan penelitian ini sebanyak 11 siswa. Teknik pengambilan sampel dalam riset ini menggunakan teknik purposive Sampling.Uji hipotesis pada riset ini menggunakan uji paired samples t-test. Berdasarkan hasil uji hipotesis diperoleh p = ,013 (p < 0,05), maknanya layanan konseling kelompok realita efektif untuk meningkatkan tanggung jawab belajar siswa. Keterbatasan penelitian ini yaitu jumlah partisipan yang terbatas sehingga dalam menggeneralisasi hasil penelitian perlu kehati-hatian, dan dengan dimasukan unsur-unsur berbasis islam dalam konseling kelompok realita realita berpotensi membatasi generalisasi hasil penelitian ini di semua agama. Peneliti selanjutnya disarankan untuk mengunakan populasi dengan cakupan yang lebih banyak, termasuk siswa yang berlatar belakang agama yang beragam dan mengeksplorasi konseling kelompok realita tanpa unsur islam untuk mengetahui dampaknya terhadap tanggung jawab belajar siswa dari berbagai latar belakang agama.